Android Based Application to Ensure Medical Adherence: CareWise - Anushka Prashant Amte; Bryan Francis; Elisha Halona Edwin Gras; Sini Anna Reji (International Journal of Engineering and Management Research, 2021)
In this fast-paced world, it is difficult to balance one’s domestic and professional life. Often, we have seen our grandparents forget things that are a part of their routine for like their medication. Many of them need to take their medicines at a fixed time, due to their age they often forget their scheduled medicines which can sometimes have consequences on their health. Therefore, we feel that there is need for an application to help our fellow senior citizens with their medication by the usage of image and a general description. By doing so we feel that this application can act as a helping hand to better monitor their health. This application will have features which will help them sort out medicines based on their name, image and description. A scheduled calendar will help them plan their medicine more efficiently. Reminders ensure that they don’t forget the medications. This application will provide a very easy to use interface that the elderly can easily navigate through without any qualms.